QUALIDADE EM SERVIÇOS DE DISTRIBUIÇÃO PARA O MERCADO FOODSERVICE: UM ESTUDO DE CASO - Freitas, Carlos Roberto de (2012)
The market for food away from home (foodservice) has grown rapidly in Brazil, and with it the need to provide better services. The main objective of this work is to identify by soght the customer critical success factors, a distributor of products for the foodservice market, located in the city of Juiz de For a, which operates in this business since 1974. The work begins with a background on the topic foodservice. The literature review is made on the issues, services, services, quality, services, processes, services, models for measuring quality in service, critical success factors, supply chain management and logistics as a competitive advantage. The research was done with a universe of 3000 customers in the Zona da Mata region of Minas Gerais, part of the metropolitan region of Belo Horizonte, Field of Strands and part of the southern mountainous region of Rio de Janeiro. The methodology used was the case study. The basis for the development of the work was the research tool in service quality SERVQUAL. Were answered over 200 questionares on the quality of service provided to customers by company XYZ transformers foodservice market (bakeries, restaurants, hotels, etc.). The survey results were considered favorable to the company researched since the results showed a good degree of customer satisfaction in relation to services rendered.